Psychological Factors and Their Effect on the Health, Well-Being and Performance of Athletes - Gómez-López, Manuel; Bianco, Antonino; da Silva, Carlos Marques (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Regular sports practice has a positive influence on the physical, mental, and psychological health of athletes at different levels and in a variety of contexts. Sports performance depends not only on the physical qualities of athletes, but also on psychological variables. In a competitive context, knowledge and manipulation of psychological variables such as attention, self-confidence, stress control, anxiety, motivation, cohesion, self-control or emotional self-regulation, moods, and interpersonal skills can influence the performance and health of an athlete.This publication brings together the latest research on these psychological factors that influence sports performance, physical health, the mental and psychological well-being of athletes, and adherence to sport.